Legal Implication Analysis of Decision Number 14/Pdt.G.S/2022/PN.Gto On The Legal Protection of Creditors Against Bad Debts Burdened By Fiduciary Guarantees - Seli Anggarani Kasih; Pujiyono; Noor Saptanti (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to examine how legal protection for creditors is applied in judicial practice by analyzing the case in Decision Number 14/Pdt.G.S/2022/PN.Gto. It focuses on the legal protection available to creditors when a debtor defaults (bad debt) on a financing agreement secured by a fiduciary guarantee. This research is crucial as it highlights how the law provides a foundation for protection by recognizing agreements, establishing breach of contract (default), and granting rights over the collateral object.On the other hand, the evidentiary process in court and disputes surrounding the formal aspects of the guarantee show that such legal protection does not always run smoothly and can be influenced by various factors. Consequently, there is an urgent need to analyze the considerations weighed by the panel of judges in bad debt cases secured by fiduciary guarantees.This study utilizes a normative legal research method (doctrinal) by analyzing applicable legal regulations supported by other legal materials, including primary and secondary sources. The findings demonstrate that fiduciary guarantees are fundamentally recognized and enforced by courts through civil dispute resolution mechanisms. However, the implementation of this legal protection varies depending on the concrete circumstances of the case, particularly when disputes arise regarding the formal validity of the fiduciary guarantee that serves as the basis for protecting the creditor’s rights.